Peran Self Control terhadap Perilaku Aggressive Driving Pengguna Sepeda Motor - Muhammad Wika Kurniawan; Indra Prapto Nugroho (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
The aim of the study is determining whether there is a role of self control toward aggressive driving behavior on motorcyclist. This study hypothesizes that there is a role of self control toward aggressive driving behavior on motorcyclist. This study used 200 young male motorcyclists in South Sumatera as participants who already has driving license C and used 50 motorcyclists as the trial participants. The sampling technique was purposive sampling. The study measurements are self control scale and aggressive driving behavior scale that refer to Averill’s (1973) self control types and Tasca’s (2000) aggressive driving behavior forms. Data analysis used simple regression.The result of simple regression shows R square = 0,507, F= 203,680, and p = 0,000 (p<0,05). This means that self control has a significant role toward aggressive driving behavior. Thus, the hypothesis could be accepted and self control contribution toward aggressive driving behavior is 50,7%.